2002
DOI: 10.1034/j.1600-0749.2002.02051.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Human Melanocortin 1 Receptor Expression in Epidermal Melanocytes by Paracrine and Endocrine Factors and by Ultraviolet Radiation

Abstract: The aim of this study is to investigate the regulation of the human melanocortin 1 receptor (MC1R) expression in cultured normal human melanocytes (NHM) by specific paracrine and endocrine factors, and by ultraviolet radiation (UVR). Treatment of NHM with alpha-melanotropin [alpha-melanocyte stimulating hormone (alpha-MSH)] increased MC1R mRNA level; the response was often more pronounced in NHM with a low (NHM-c) than in NHM with a high melanin content (NHM-b). Endothelin-1 increased MC1R mRNA level in NHM re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 47 publications
3
113
0
4
Order By: Relevance
“…Se o MC1-R está envolvido em outras vias sinalizadoras, ainda permanece desconhecido, mas a ativação do MC1-R influencia as quantidades relativas de feomelanina e eumelanina produzidas, sendo sua perda de atividade, associada a cabelos vermelhos ou amarelos. 20,34,38,39,[48][49][50][51][52] Variantes do MC1-R têm sido associadas com a herança de cabelo vermelho, na qual mais pigmento amarelo-avermelhado de feomelanina é produzido e apresentam capacidade de bronzeamento muito pequena. Variantes R160W, R151C, D294H, R142H, 86insA e 537insC de MC1-R são os principais determinantes do fenótipo de cabelos vermelhos e pele clara.…”
Section: Melaninaunclassified
See 1 more Smart Citation
“…Se o MC1-R está envolvido em outras vias sinalizadoras, ainda permanece desconhecido, mas a ativação do MC1-R influencia as quantidades relativas de feomelanina e eumelanina produzidas, sendo sua perda de atividade, associada a cabelos vermelhos ou amarelos. 20,34,38,39,[48][49][50][51][52] Variantes do MC1-R têm sido associadas com a herança de cabelo vermelho, na qual mais pigmento amarelo-avermelhado de feomelanina é produzido e apresentam capacidade de bronzeamento muito pequena. Variantes R160W, R151C, D294H, R142H, 86insA e 537insC de MC1-R são os principais determinantes do fenótipo de cabelos vermelhos e pele clara.…”
Section: Melaninaunclassified
“…51 Além disso, em estudo recente demonstrou-se uma expressão aumentada de receptores estrogênicos na pele com melasma, comparada à pele normal, porém a avaliação foi de apenas dois pacientes e de forma qualitativa, o que não permite ainda determinar a real função deste receptor e do estrogênio na fisiopatogenia do melasma. 82 …”
Section: Melasmaunclassified
“…Most studies have proposed that ASP acts as an antagonist of MC1R, causing MC1R desensitization and consequent reduction of tyrosinase activity. 4,17 However, Scott et al 18 observed that ASP plays a role in the regulation of skin pigmentation through downregulation of MC1R mRNA transcription in cultured human melanocytes. Recently, microphthalmia transcription factor (MITF), which belong to the basic helix-loop-helix family, was found to regulate the gene for MC1R through its promoter region in cultured cells.…”
Section: Seeing the Gene Therapy C-h Yang Et Almentioning
confidence: 99%
“…UV also induces melanin stimulating hormone locally from keratinocytes; such paracrine secretion plays a critical role in local cell regulation from an immunosuppressive and proinflammatory point of view [281,321]. The receptor for pigment regulation within melanocytes, melanocortin receptor, is also regulated by UV [281,322]. 31 The mechanisms underlying immune responsiveness following UV have earlier been reviewed [323].…”
Section: Immunosuppressive Effects Of Large Uv Exposuresmentioning
confidence: 99%